Optimization of pectin extraction from saba banana (musa paradisiaca linn. var. compressa) peels - Felisilda, Roffell D. (College of Home Economics, University of the Philippines Diliman, 2010)
ABSTRACT A completely randomized two-factor experimental design was used to investigate the effect of extraction time (30 minutes, two consecutive 30 minutes, and 1 hour) and temperature (60°C, 75°C, and 90°C) on the % yield and degree of esterification of pectin from Saba banana (Musa paradisiaca Linn. var. compressa) peels. The results were used to determine the best conditions for the extraction of pectin. It was found out that the extraction temperature was the only factor that was able to significantly influence the parameters observed. Increasing the extraction temperature resulted in a significant increase in the amount of extracted pectin material, but with a considerable decrease in the degree of methylation. Acid extraction at 60°C both for two consecutive 30 minutes and 1 continuous hour was found to be the most protective process, yielding acceptable amounts of pectin (0.29% and 0.35% respectively) with the highest amount of esterified methyl groups (18.87% and 29.05%).